Radiology in gastroenterology (According to data of the 16th Russian gastroenterological week, Moscow, October 11–13, 2010) - Z. A. Lemeshko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of publication. To reflect state-of-the-art of radiology in gastroenterology.Original positions. Potentials of modern radiology at diseases of biliary tracts, liver, pancreas, gastrointestinal tract, front abdominal wall, etc. are analyzed according to the data of The 16-th Russian gastroenterological week which was held in Moscow October, 11–13, 2010. Features of application of ultrasound investigation, roentgenologic procedures, magnetic-resonance tomography as stand alone methods and at complex investigation are underlined. Algorithms of diagnostics of various diseases, noninvasive medical procedures are proposed. Attention is drawn to necessity of contrast agents application, software improvements and conservation of obtained information is inverted.Conclusion. The further improvement and application of modern radiological methods of investigation will promote improvement of diagnostics of diseases of digestive organs that allows to prescribe adequate treatment and to provide correct patient management approach.